2011
DOI: 10.3945/jn.110.137323
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated Coffee Does Not Acutely Affect Energy Intake, Appetite, or Inflammation but Prevents Serum Cortisol Concentrations from Falling in Healthy Men1–4

Abstract: Our aim in this crossover study was to investigate the acute effects of caffeinated and decaffeinated coffee consumption on appetite feelings, energy intake, and appetite-, inflammation-, stress-, and glucose metabolism-related markers. Sixteen healthy men (age range, 21-39 y; BMI range, 19.7-28.6 kg/m(2)) received in a random order on 3 separate occasions a standard breakfast snack with 200 mL of either caffeinated coffee (3 mg caffeine/kg body weight), decaffeinated coffee, or water (control). Before interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 27 publications
(32 reference statements)
6
48
2
4
Order By: Relevance
“…In addition, it was noted that included caffeine in coffee inhibits evening decrease in cortisol levels. This effect is more pronounced in younger group (15-40 years) than in older (41-70 years), regardless of gender [73][74][75]. Fig.…”
Section: Dietary Supplementsmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, it was noted that included caffeine in coffee inhibits evening decrease in cortisol levels. This effect is more pronounced in younger group (15-40 years) than in older (41-70 years), regardless of gender [73][74][75]. Fig.…”
Section: Dietary Supplementsmentioning
confidence: 77%
“…In contrast to the green, black coffee stimulates secretion of hydrocortisone. Studies of Gavrieli et al [74] on cortisol levels in men who drank decaffeinated and caffeine-containing coffee showed that for the impact on level of this hormone is responsible caffeine. In addition, it was noted that included caffeine in coffee inhibits evening decrease in cortisol levels.…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…In our trial with overweight subjects, no significant effects on body weight were found either, although we observed a significantly higher weight loss in those subjects with higher serum NMP levels after coffee consumption phase. Previous studies of acute responses to coffee intake reported counteracting effects on dietary intake and appetite [27,28] and thus indicate that additional factors might determine coffee-influenced weight development. This hypothesis is supported by results from a pilot study with 29 healthy volunteers, where after daily consumption of 750 ml coffee for 4 weeks, an increased Nrf2 transcription in peripheral blood lymphocytes had been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Predisposing genetic factors may include common variants on single nucleotide polymorphisms (SNPs) in genes associated with cortisol metabolism (SRD5A2) (Steen et al 2010), the regulation of cortisol (glucocorticoid receptor, NR3C1) (Schatzberg et al 2014), dopamine catabolism (catechol-omethyltransfease COMT; dopamine D4 receptor gene (DRD4) (Jabbi et al 2007), inhibitory neurotransmittors (GABA a6 receptor subunit gene; GABRA6) (Uhart et al 2004) and stress-vulnerability (serotonin transporter-linked polymorphic region; 5-HTTLPR) (Miller et al 2013). Similarly, environmental factors such as substance abuse (Lopez-Larson et al 2011;Gavrieli et al 2011), sleep deprivation (Spiegel et al 1999), dietary changes (Cheng and Li 2012), lower socioeconomic status (Rudolph et al 2014) and a lower level of education (Karlamangla et al 2013) may contribute to the increased cortisol. While it remains unclear whether elevated cortisol levels are a risk factor for these disorders or a consequence of onset, recent studies suggest that it may be an interaction of the two (Wang et al 2011;Aina 2013;Perroud et al 2011).…”
Section: Levels Of Cortisol In Schizophrenia and Bipolar Disordermentioning
confidence: 99%